2010
DOI: 10.1111/j.1464-5491.2010.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of best practice guidelines for the genetic diagnosis of MODY2 and MODY3

Abstract: trainees, and this will also spread the workload of teaching across the entire team rather than being consultant-led only. Our pilot study clearly emphasizes the need for incorporating more dedicated sessions in teaching schedules to assist medical students in achieving their intended learning outcomes and to empower them with the insight about the specialty to drive further interest for future career choices. References1 Murphy RJ, Gray SA, Straja SR, Bogert MC. Student learning preferences and teaching impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Maturity Onset Diabetes of the Young (MODY), a monogenic diabetes inherited in an autosomal dominant mode, accounts for 1–2% of all diabetes forms in Europe [1], [2]. It is a clinically heterogeneous group of diseases caused by at least eight gene defects in the pancreatic β-cell that impair insulin secretion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Maturity Onset Diabetes of the Young (MODY), a monogenic diabetes inherited in an autosomal dominant mode, accounts for 1–2% of all diabetes forms in Europe [1], [2]. It is a clinically heterogeneous group of diseases caused by at least eight gene defects in the pancreatic β-cell that impair insulin secretion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a rationale search for different forms of diabetes is justified only when type 1 diabetes has been excluded. Although this strategy is not included in the EMGQN guidelines [5] , many researchers and clinicians apply it [13] , [14] , [17] , [18] . Regarding insulin treatment, most MODY2 patients have a modest impairment of glucose metabolism and usually do not need pharmacological intervention [17] .…”
Section: Discussionmentioning
confidence: 99%
“…This criterion was included because MODY2 is an autosomal dominant inherited disease, with rare de novo mutations described [17] . Familiarity is not mandatory in the EMGQN guidelines [5] , however recent studies found that it is the most powerful factor in distinguishing between MODY and sporadic forms of diabetes [10] , [13] , [14] . Furthermore, because MODY2 is usually discovered during infancy or in early adulthood, a diagnosis before 25 years of age is a criterion for the test in the 7-iF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of antibodies to pancreatic islets in the monogenic diabetes remains unknown and the incidence estimation is difficult as the occurrence of autoantibodies in the patient is one of the well-known exclusion criteria for further genetic diagnostics [1][2][3]. This approach can lead to an underestimation and unreliably respond to the matter of the humoral response markers in diabetes of non-autoimmune etiology.…”
Section: Introductionmentioning
confidence: 99%